2008
DOI: 10.1086/590330
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Modeling of the Radio Torus Surrounding SN 1987A

Abstract: We present detailed Fourier modeling of the radio remnant of SN 1987A using high-resolution 9 and 18 GHz data taken with the Australia Telescope Compact Array over the period 1992-2008. We develop a parameterized threedimensional torus model for the expanding radio shell, in which the emission is confined to an inclined equatorial belt; our model also incorporates both a correction for light-travel time effects and an overall east-west gradient in the radio emissivity. By deriving an analytic expression for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 48 publications
(103 reference statements)
9
60
1
Order By: Relevance
“…The three-dimensional effects and emission regions also likely differ between these components. Ng et al (2008) predict that they will soon see a deceleration in the radio remnant expansion similar to that we have observed from the X-ray remnant due to the forward shock interacting with the optical inner ring.…”
Section: Resultssupporting
confidence: 73%
“…The three-dimensional effects and emission regions also likely differ between these components. Ng et al (2008) predict that they will soon see a deceleration in the radio remnant expansion similar to that we have observed from the X-ray remnant due to the forward shock interacting with the optical inner ring.…”
Section: Resultssupporting
confidence: 73%
“…1), making it the highest radio frequency at which this has now been accomplished. The 3-mm image shows similarities with the images at 7 and 12 mm (Manchester et al 2005;Potter et al 2009) and at 3 cm (Ng et al 2008). The emission is broadly distributed along the equatorial ring, but unlike the optical images the radio appearance is asymmetric with the emission peaking in the eastern lobe (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…The flux ratio between the eastern and western halves of the image is ≈1.3. By fitting an optically thin shell, this asymmetry was found to be ≈1.3 at 7 mm (Potter et al 2009) and ≈1.4 at 3 cm (Ng et al 2008). The maximum asymmetry with respect to the VLBI position in the 3-mm image occurs near position angle 90…”
Section: Discussionmentioning
confidence: 88%
“…The dotted vertical line marks the current epoch. The observed radius and speed of the SN shock, as determined by radio observations (Ng et al 2008), are shown as well. The scaling values are R i = R T = 3.1 × 10 17 cm and V i = 28,000 km s −1 .…”
Section: Particle Acceleration Modelmentioning
confidence: 79%